Optimization and Standardization of the Immunodeficient Mouse Model for Assessing Fat Grafting Outcomes. Issue 6 (December 2017) - Kokai, Lauren E.; Jones, Taraneh L.; Silowash, Russell; Theisen, Brian; DiBernardo, Gabriella; Lu, Andrew; Yi, Bowen; Marra, Kacey G.; Rubin, J. Peter
Abstract : Background: Animal models are often used to assess interventions that might improve fat grafting outcomes; however, there is great variability in the models. The authors sought to determine the predictive value of the immunocompromised mouse model for fat grafting so that experiments could be standardized and optimized. Methods: Human lipoaspirate injections at different volumes and time points were assessed in a nude mouse model and compared with control injections of nonviable fat. Volume retention and explant histologic score were compared. In a separate study, interanimal reproducibility was determined by implanting a highly consistent hydrogel and measuring variability in volume retention. Results: Injection volume significantly affects adipose resorption kinetics at 6 and 12 weeks. Masson trichrome staining revealed that macrophages were unable to infiltrate large (1 ml) grafts, and oil cysts were not absorbed by 18 weeks, which interfered with interpretation of volume retention data. Nonviable tissue was resorbed when grafts were 0.3 ml, and quantification of graft histologic viability correlated well with graft retention at all study time points. Interanimal variability was measured to be 8.44 percent of the mean retention volume for small graft volumes. Conclusions: Human fat graft retention in the immunodeficient mouse correlates with graft viability in small, 0.3-ml-volume grafts. However, centralized oil cysts in nonviable 1.0-ml grafts were not resorbed by 18 weeks and thus volume measurements were confounded and not significantly different from viable samples. In addition, tissue injury scores increased in initially healthy fat grafts at 18 weeks, possibly because of a delayed immune reaction. Abstract : Supplemental Digital Content is available in the text.